Un probleme d'identification de parametre associe aux equations de Saint-Venant - ldrissi, Mekki; Soulaimani, Azzeddine (European Journal of Computational Mechanics, 1997)
This work presents a numerical method to automatically identify the friction coefficient which governs natural free suiface flows. The mathematical formulation is based on the optimal control theory. A Lagrangian operator, which partial derivatives provide respectively the state equations, the adjoint equations and the optimality condition, is introduced. A finite element method is used for space discretization. Two solution algorithms are proposed and tested on some steady flows. The first one is very robust and converges for any initial distribution of the friction coefficient. The second one converges for realistic initial trials, uses less memory and could be well extended to unsteady flows.